Empirical investigation of foreign direct investment and current account balance in East Asian economies - Mahnaz Ali; Tusawar Iftikhar Ahmad; Rozina Sadiq (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Among the Asian regions the East Asia is the largest recipient of foreign direct investment (FDI). The FDI by affecting the host country's exports and imports may also influence the current account balance (CAB) of that country. The East Asian economies are facing the persistent current account deficit. The current study investigates the impact of FDI inflows on CABand on its components (exports and imports) for a panel of selected East Asian economies. The study employs System Generalized Method of Moments (Sys GMM) estimation technique on a panel of five countries for the years 2000-2016. FDI is found to have negative effect oncurrent account deficit and positive effect on exports and imports of the selected economies. It is concluded that by improving the host country's exports, FDI inflows can improve CAB in case of East Asian selected economies.
Keywords: 330; FDI inflows; Current account deficit; Exports; Imports; East Asia